2006
DOI: 10.1002/nau.20293
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of overactive bladder syndrome in Fuzhou Chinese women

Abstract: The prevalence of OAB in chinese women is lower than that of most reports in Occidental women, and increases with advancing age. Many potential risk factors increase the occurrence of OAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
6
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 16 publications
7
66
6
6
Order By: Relevance
“…16 In Asian courtiers, the prevalence of OAB in women aged ≥ 18 years was reported to be 53.1% by use of a different definition of OAB, which was the presence of frequency, urgency and urgency incontinency either single or in combination. 17 Among individual with OAB, 66.7% suffer from OAB dry and 33.3% suffer from OAB wet in our study, which is consistent with the result of Zhang et al 18 , but contrary to the results of NOBLE study.…”
Section: Discussionsupporting
confidence: 82%
“…16 In Asian courtiers, the prevalence of OAB in women aged ≥ 18 years was reported to be 53.1% by use of a different definition of OAB, which was the presence of frequency, urgency and urgency incontinency either single or in combination. 17 Among individual with OAB, 66.7% suffer from OAB dry and 33.3% suffer from OAB wet in our study, which is consistent with the result of Zhang et al 18 , but contrary to the results of NOBLE study.…”
Section: Discussionsupporting
confidence: 82%
“…In view of the use of multiple variables in a small sample without adjusted logistic regression analysis, there is a significant risk of overfitting M a n u s c r i p t 11 for this scoring system. In our model parity ≥ 2 rather than nulliparity was a predictor of DO and our findings are consistent with epidemiological research relating to OAB [28].…”
Section: Commentsupporting
confidence: 91%
“…Zhang et al concluded that the contributing risk factors are advanced age, menopause, parity >2, constipation, Hx of episiotomy, and high basal metabolic rate (BMI) [95].…”
Section: Vitamin D and Overactive Bladdermentioning
confidence: 99%